2000
DOI: 10.1152/ajplung.2000.278.6.l1180
|View full text |Cite
|
Sign up to set email alerts
|

Increased lung expansion alters the proportions of type I and type II alveolar epithelial cells in fetal sheep

Abstract: Type I and type II alveolar epithelial cells (AECs) are derived from the same progenitor cell, but little is known about the factors that regulate their differentiation into separate phenotypes. An alteration in lung expansion alters the proportion type II AECs in the fetal lung, indicating that this may be a regulatory factor. Our aim was to quantify the changes in the proportion of type I and type II AECs caused by increased fetal lung expansion and to provide evidence for transdifferentiation of type II int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
130
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(138 citation statements)
references
References 15 publications
7
130
1
Order By: Relevance
“…The current studies show that decreased distension not only retards lung growth but also inhibits differentiation of type I cells. Previous studies have shown that increased lung distension in fetal sheep accelerates lung growth and decreases numbers of type II cells and surfactant (2,11,18,28,32,37). The cellular mechanisms involved in the responses to changes in distension of the fetal lung have not been defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current studies show that decreased distension not only retards lung growth but also inhibits differentiation of type I cells. Previous studies have shown that increased lung distension in fetal sheep accelerates lung growth and decreases numbers of type II cells and surfactant (2,11,18,28,32,37). The cellular mechanisms involved in the responses to changes in distension of the fetal lung have not been defined.…”
Section: Discussionmentioning
confidence: 99%
“…However, they reported neither quantitative data for cell counts nor measurements of indicators of surfactant, which is produced by type II cells. Subsequently, other investigators have studied tracheal ligation in fetal sheep and have confirmed that an increase in lung distension results in a lower number of type II cells (6,11,37) and a higher percentage of type I cells (18). Tracheal ligation also results in lower concentrations in the lung of surfactant protein (SP)-A and saturated phosphatidylcholine (SatPC), the major surface-active lipid in pulmonary surfactant (28), as well as mRNA for SP-A, -B, and -C (32).…”
mentioning
confidence: 92%
“…Experiments performed primarily in fetal sheep have demonstrated that prolonged TO (Ďž2 wk) leads to an almost total loss of the surfactant-producing alveolar epithelial type II (AE2) cells (4,13,14). During fetal lung development, AE2 cells are thought to act as precursors for AE1 cells (32).…”
mentioning
confidence: 99%
“…During fetal lung development, AE2 cells are thought to act as precursors for AE1 cells (32). Furthermore, the differentiation of AE2 cells into AE1 cells is strongly influenced by local distending forces within the lung, such that increased levels of lung tissue stretch accelerate the differentiation of AE2 cells to AE1 cells (4,13,14). Consequently, the lungs of animals that have undergone prolonged fetal TO are "stiff" and unable to function effectively in respiratory gas exchange (25).…”
mentioning
confidence: 99%
“…Conditions that are associated with lung liquid drainage are characterized by pulmonary hypoplasia and an excess of type II cells (Flecknoe et al, 2003;Laudy and Wladimiroff, 2000). Hypoplasia is reversible with tracheal ligation, where presumed accumulation of lung fluid induces rapid lung growth and changes in alveolar structure (Flecknoe et al, 2000). In order to differentiate between the actual cellular growth of the graft vs. the increase in size due to fluid accumulation and/or fusion of grafts, ICC for proliferation marker (PCNA) was performed.…”
Section: Discussionmentioning
confidence: 99%